2018
DOI: 10.1103/physrevd.98.045010
|View full text |Cite
|
Sign up to set email alerts
|

Particle decay in expanding Friedmann-Robertson-Walker universes

Abstract: The lack of energy conservation introduces new particle processes in curved spacetime that are forbidden in flat space. Therefore one has to be very cautious about using the results calculated in Minkowskian space in early universe applications. This is true for particle decay rates in particular, which need to be calculated using quantum field theory in curved spacetime. Previous studies are usually restricted to using minimal or conformal coupling for the decaying particle, while using a more general couplin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 29 publications
(66 reference statements)
0
44
0
Order By: Relevance
“…It was found that Minkowskian and curved space decay rates produce results within the same order of magnitude with only small numerical differences. Although it is known that decay rates in curved space are modified from their Minkowskian counterparts [20,21,24], it is likely that the timescales in question are so small that the effect of curved space modification has not produced noticeable effects yet.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that Minkowskian and curved space decay rates produce results within the same order of magnitude with only small numerical differences. Although it is known that decay rates in curved space are modified from their Minkowskian counterparts [20,21,24], it is likely that the timescales in question are so small that the effect of curved space modification has not produced noticeable effects yet.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…First of all, the parameter b affects only the evolution of the energy densities in the stiff matter phase. From previous works on particle decay, we know that the decay rate for the massive scalar to decay into massless scalars is faster the more massive the particle is [20,22]. It is therefore reasonable to expect that both energy densities, massive and massless, follow closely one another in the stiff matter phase regardless of the mass of the particle.…”
Section: Reheating Temperaturementioning
confidence: 96%
See 2 more Smart Citations
“…(III. 33) In perturbation theory there is a complex pole very near ω = 0 which can be obtained directly by expanding the integral in the denominator near ω = 0. We find…”
Section: B Non-perturbative Methodsmentioning
confidence: 99%